Hypertension (HTN) as a potential biomarker of efficacy in pazopanib-treated patients with advanced non-adipocytic soft tissue sarcoma. A retrospective study based on European Organisation for Research and Treatment of Cancer (EORTC) 62043 and 62072 trials. Issue 17 (November 2015) - Duffaud, F.; Sleijfer, S.; Litière, S.; Ray-Coquard, I.; Le Cesne, A.; Papai, Z.; Judson, I.; Schöffski, P.; Chawla, S.P.; Dewji, R.; Marreaud, S.; Verweij, J.; et al.
Highlights: Pazopanib is an active agent for metastatic non-adipocytic soft tissue sarcomas. Markers to early identify patients benefiting from treatment are needed. Hypertension (HTN) is a specific side-effect of pazopanib. In 337 patients the association of occurrence of HTN and outcome was assessed. No association was found between the occurrence of HTN and outcome. Abstract: Background: Reliable biomarkers of pazopanib's efficacy in soft tissue sarcoma (STS) are lacking. Hypertension (HTN) is an on-target effect of vascular endothelial growth factor (VEGF)-receptor inhibitors such as pazopanib. We evaluated the association of pazopanib-induced HTN with antitumour efficacy in patients with metastatic non-adipocytic STS. Methods: Associations between pazopanib-induced-HTN and antitumour efficacy were retrospectively assessed across 2 prospective studies (European Organisation for Research and Treatment of Cancer (EORTC) study 62043 and 62072) in metastatic STS patients who received pazopanib 800 mg daily. Only patients with baseline blood pressure (BP) < 150/90 mmHg, were included. BP was measured monthly. HTN was reported according to National Cancer Institute-Common Toxicity Criteria Adverse Events (NCI-CTC AE) grading (v3.0), and as absolute differences compared to baseline. The effect of HTN developing in patients without baseline anti-hypertensive medication was assessed on progression-free (PFS) and overall survival (OS) using a landmark analysis stratified by study; univariately using the Kaplan–Meier method and a log-rank test, and in a multivariate Cox regression model after adjustment for important prognostic factors. Results: Of the 337 patients eligible for this analysis, 21.7% received anti-hypertensive medication at baseline and had a similar PFS and OS compared to those who did not. In patients without baseline anti-hypertensive medication, 38.6% developed HTN. As the majority of patients developing HTN did so within 5 weeks after initiation of pazopanib (68.6%), this time point was used as landmark. Univariately, there was no effect on PFS or OS from occurrence of HTN within 5 weeks of treatment expressed either in NCI-CTC AE criteria or as maximal differences from baseline in systolic and diastolic BP. Also in multivariate analysis, after adjusting for important prognostic factors, the occurrence of HTN expressed in the different parameters was not associated with PFS and OS. Conclusions: In this retrospective analysis, pazopanib-induced HTN did not correlate with outcome in pazopanib-treated STS patients. The occurrence of HTN cannot serve as biomarker in this setting.